2018
DOI: 10.1093/sysbio/syy047
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Rates for Phylogenetic Inference and Experimental Design in the Era of Genome-Scale Data Sets

Abstract: With the rise of genome- scale datasets there has been a call for increased data scrutiny and careful selection of loci appropriate for attempting the resolution of a phylogenetic problem. Such loci are desired to maximize phylogenetic information content while minimizing the risk of homoplasy. Theory posits the existence of characters that evolve under such an optimum rate, and efforts to determine optimal rates of inference have been a cornerstone of phylogenetic experimental design for over two decades. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 74 publications
6
74
2
Order By: Relevance
“…In contrast to expectations of how markers from different genomic subsets are useful in phylogenetics studies (Dornburg, Su, and Townsend 2019;Steel and Leuenberger 2017;Phillips, Delsuc, and Penny 2004) , seven of the nine locus types showed broad phylogenetic utility over the timescales associated with this study. Intronic sites were moderately more informative for younger nodes in the rodent and combined datasets, while CDS sites had a stronger trend towards informativeness in older nodes among pecora, rodents, and the combined dataset.…”
Section: Phylogenetic Informativeness Of Most Locus Types Is Stable Acontrasting
confidence: 92%
See 1 more Smart Citation
“…In contrast to expectations of how markers from different genomic subsets are useful in phylogenetics studies (Dornburg, Su, and Townsend 2019;Steel and Leuenberger 2017;Phillips, Delsuc, and Penny 2004) , seven of the nine locus types showed broad phylogenetic utility over the timescales associated with this study. Intronic sites were moderately more informative for younger nodes in the rodent and combined datasets, while CDS sites had a stronger trend towards informativeness in older nodes among pecora, rodents, and the combined dataset.…”
Section: Phylogenetic Informativeness Of Most Locus Types Is Stable Acontrasting
confidence: 92%
“…homoplasy) over longer evolutionary timescales (Managadze et al 2011;Goldman and Yang 1994;Hughes and Yeager 1998;Bromham, Rambaut, and Harvey 1996;Ren et al 2016;Salichos and Rokas 2013;Dornburg et al 2014) . While this marker selection strategy appears reasonable, studies of the relationship between rate and phylogenetic utility are often complicated by interacting factors (Aguileta et al 2008;Townsend and Leuenberger 2011;Dornburg, Su, and Townsend 2019;Steel and Leuenberger 2017;Heath et al 2008;Su and Townsend 2015) .…”
Section: Introductionmentioning
confidence: 99%
“…While no studies have directly examined the impact of model complexity on time estimation in phylogenomic investigations, there have been reports that simple substitution models often perform similarly to or slightly worse than complex substitution models in some types of phylogenetic inferences (Tamura et al 2004;Yoshida and Nei 2016;Dornburg et al 2018;Spielman and Kosakovsky Pond 2018;Abadi et al 2019;Spielman 2019). However, in molecular dating, it is intuitively assumed that underestimation of sequence divergence caused by the use of simple models will result in significantly distorted time estimates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we and others have demonstrated that employing the most parameter-rich model, GTR+I+G, leads to topology reconstructions that are as accurate as those produced by established model selection strategies (Arbiza et al 2011;Abadi et al 2019;Spielman 2019). On the other hand, for the tasks of branch-length and divergence time estimations it was shown that the accuracy is conditioned on the selected model and so model selection should still be advocated (Buckley et al 2001;Posada 2001;Minin et al 2003;Abdo et al 2005;Spielman and Kosakovsky Pond 2018;Dornburg et al 2019). For example, Abadi et al (Abadi et al 2019) demonstrated that the consistent use of GTR+I+G generally results in inferior branch-length estimates compared to those obtained by model selection criteria, with the BIC and DT criteria obtaining the most accurate estimates.…”
Section: Introductionmentioning
confidence: 98%